Reverse logistics-- The Warehouse Ltd as a case study : a thesis presented in partial fulfillment of the requirements for the degree of Master of Applied Science in Logistics and Supply Chain Management at Massey University - Sachdev, Deepak Amar (Massey University, 2007)
Supply chain perspective identifies with systems thinking, as its emphasis is on holistic management. Supply chain tactics and strategies include decisions on the activities of planning, procurement, production, logistics, warehousing and sales (including returns). Given the differences between forward and reverse logistics, it is important to structure reverse logistics accordingly to derive maximum benefit. Customer returns is a key component of reverse logistics for any retailer. This thesis takes a case study approach to the customer returns processes of reverse logistics, at The Warehouse Ltd. (TWL), New Zealand. The approach is one of description of customer returns related Reverse logistics processes to meet the objective of "what is happening?" at the largest general merchandise retailer in New Zealand. Thus research presented in this thesis relates to an in-depth description of the reverse logistics process. Also presented is an analysis of overall return trends, department levels and grouped data for Jan 06. There is a seasonal trend of peak returns post Christmas and the returns show a decreasing trend. At TWL, the reverse logistics process starts at the returns desk. The customer brings the product to the returns desk at a store, based on the nature of product it may then return to the sales floor or the stockroom. From the stockroom, it may be sent to a repair agent or the reverse logistics distribution center or to landfill. When it reaches the reverse logistics distribution center (RDC), based on the reason of return and the state of the product it is either allocated for landfill, supplier credit or auction. Conclusion, management comments, options and potential further research areas are included.
Keywords: Warehouse Group; Logistics; Returning goods